A high-throughput LC–MS/MS assay for quantification of artesunate and its metabolite dihydroartemisinin in human plasma and saliva. (September 2014) - Birgersson, Sofia; Ericsson, Therese; Blank, Antje; Hagens, Cornelia von; Ashton, Michael; Hoffmann, Kurt-Jürgen
Aim: Saliva is an alternative sampling matrix to plasma, offering a noninvasive technique, but requires a highly sensitive bioanalytical method.Materials & methods: An API 3000 triple quadrupole mass spectrometer with an electrospray ionization source operated in the positive ion mode was used for the analysis.Results: A high-throughput LC–MS/MS method using SPE for the quantification of artesunate and dihydroartemisinin in plasma and saliva has been optimized and validated according to US FDA guidelines. For both analytes the LLOQ was determined to 5 ng/ml and the calibration range was 5–1000 ng/ml for artesunate and 5–2000 ng/ml for dihydroartemisinin.Conclusion: For the first time, a bioanalytical method for determination of artesunate and dihydroartemisinin in human saliva has been described, showing possible applicability in clinical saliva samples in addition to plasma samples.